Chromosomal Microarray Testing For Children With Unexplained Neurodevelopmental Disorders. Issue 11 (November 2017) - Martin, Christa Lese; Ledbetter, David H.
Abstract : (Abstracted from JAMA 2017;317(24):2545–2546) Chromosomal microarray analysis (CMA) has emerged as a robust means to detect chromosomal abnormalities including unbalanced chromosomal rearrangements, as well as smaller chromosomal abnormalities than those detectable by karyotype. Chromosomal microarray analysis has replaced conventional G-banded karyotyping due to its greater sensitivity and resolution; G-banding effectively identifies imbalances of DNA greater than 5 to 10 megabases (millions of base pairs), whereas CMA can detect genome-wide imbalances of more than 400 kilobases (thousands of base pairs).